The Ovals Engraved in the Adrar of Iforas (Mali) and their Saharan Counterparts.On the Trail of the Genies of African Protohistory - (:unkn) unknown (My University, 2021)
A contextual study of fifty-nine roughly oval-shaped rock engravings, sometimes decorated and provided with peripheral features, recorded in situation in the north western area of the Adrar des Iforas. Nearly four hundred comparable motifs are known in the Saharan strip from the Niger-Chad border to the Atlantic coast. A terracotta figurine from the Lower Tilemsi, and twelve stone statuettes from the southern Algerian Sahara can be compared to these engravings based on morphological and stylistic criteria. The iconographic and archæological contexts of these engravings allow us to situate their realization between the end of the Vth millennium and the middle of the IInd millennium BC. The aridity then increased. Animal husbandry became used, and Millet was cultivated in the Malian Sahara. The agro-pastoral economy tipped West Africa into protohistory. The quasi-systematic exposure of the ovals to the sky, their chimerical character, their intermeshing of animal and human figures, the parallels that are established between the iconography they belong to, and data drawn from West African ethnography, all lead us to see representations of genies perhaps connected to rain.
Keywords: African Research